2021
DOI: 10.3390/antiox10101550
|View full text |Cite
|
Sign up to set email alerts
|

Hsp22 Deficiency Induces Age-Dependent Cardiac Dilation and Dysfunction by Impairing Autophagy, Metabolism, and Oxidative Response

Abstract: Heat shock protein 22 (Hsp22) is a small heat shock protein predominantly expressed in skeletal and cardiac muscle. Previous studies indicate that Hsp22 plays a vital role in protecting the heart against cardiac stress. However, the essential role of Hsp22 in the heart under physiological conditions remains largely unknown. In this study, we used an Hsp22 knockout (KO) mouse model to determine whether loss of Hsp22 impairs cardiac growth and function with increasing age under physiological conditions. Cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 49 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…In addition, HSP22 was also found to be involved in the metabolic switch in the ischemic heart by promoting the activity of 5′ AMP-activated protein kinase (AMPK), which subsequently stimulates glucose uptake and glycolysis to compensate for the lack of aerobic ATP production in the ischemic heart [ 20 , 36 ]. A most recent study showed that loss of HSP22 impaired fatty acid (FA) and glucose metabolism by interfering with the critical regulatory enzymes in FA transport and FA oxidation (FAO) and with glycolysis and gluconeogenesis, respectively, undermining ATP production in physiological aging transition, leading to cardiac dilation and dysfunction [ 26 ].…”
Section: The Molecular Mechanisms Of Hsp22’s Cytoprotection In Cardiomyocytesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, HSP22 was also found to be involved in the metabolic switch in the ischemic heart by promoting the activity of 5′ AMP-activated protein kinase (AMPK), which subsequently stimulates glucose uptake and glycolysis to compensate for the lack of aerobic ATP production in the ischemic heart [ 20 , 36 ]. A most recent study showed that loss of HSP22 impaired fatty acid (FA) and glucose metabolism by interfering with the critical regulatory enzymes in FA transport and FA oxidation (FAO) and with glycolysis and gluconeogenesis, respectively, undermining ATP production in physiological aging transition, leading to cardiac dilation and dysfunction [ 26 ].…”
Section: The Molecular Mechanisms Of Hsp22’s Cytoprotection In Cardiomyocytesmentioning
confidence: 99%
“…BAG3 has been reported to act in concert with HSP22 to induce autophagic degradation, especially in cardiomyocytes [ 20 ]. On the other hand, a study showed that deletion of HSP22 reduced the expression of BAG3 and impaired cardiac autophagy in the aging heart [ 26 ].…”
Section: The Molecular Mechanisms Of Hsp22’s Cytoprotection In Cardiomyocytesmentioning
confidence: 99%
See 3 more Smart Citations